2009
DOI: 10.1021/es801952h
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Conjugated Natural and Synthetic Steroid Estrogens in Crude Sewage and Activated Sludge Batch Studies

Abstract: Steroids are excreted from the human body in the conjugated form but are present in sewage influent and effluent as the free steroid, the major source of estrogenic activity observed in water courses. The fate of sulfate and glucuronide conjugated steroid estrogens was investigated in batch studies using activated sludge grown on synthetic sewage in a laboratory-scale Husmann simulation and crude sewage from the field. A clear distinction between the fate of sulfate and glucuronide conjugates was observed in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 33 publications
(56 reference statements)
5
103
0
Order By: Relevance
“…The apparent biomass sorption (LogKp) values were 28 greater in the nitrifying/denitrifying works than those in the nitrifying/denitrifying works 29 with phosphorus removal for both steroid estrogens and alkylphenolic compounds 30 possibly indicating a different cell surface structure and therefore microbial population. 31 The difference in biological activity (mg tonne -1 ) identified in this study, of up to seven 32…”
mentioning
confidence: 68%
“…The apparent biomass sorption (LogKp) values were 28 greater in the nitrifying/denitrifying works than those in the nitrifying/denitrifying works 29 with phosphorus removal for both steroid estrogens and alkylphenolic compounds 30 possibly indicating a different cell surface structure and therefore microbial population. 31 The difference in biological activity (mg tonne -1 ) identified in this study, of up to seven 32…”
mentioning
confidence: 68%
“…This is most probably due to the conversion from other steroids with a similar structure, or hydrolysis of their conjugated forms (glucuronides and sulfates). 27,29 Overall, glucocorticoids had high degradation in each plant while androgens, estrogens and progestagens varied greatly between the two plants. The results from the present study showed that activated sludge treatment (Plant A) generally had a better capacity than oxidation ditch (Plant B) to degrade various steroids in sewage systems.…”
Section: Mass Balance Analysis Of Steroids In the Two Wwtpsmentioning
confidence: 99%
“…It was recognized by de Mes et al [15] that information on the role of conjugation in determining the fate of estrogens in all forms of wastewater treatment including anaerobic sludge digestion was lacking. However, it is known that sulphate conjugates are more stable than gluconarides [16]. Reports of the degradation of alkylphenol ethoxylates (APEOs) in anaerobic conditions are more scarce in comparison to steroid estrogens.…”
Section: Introductionmentioning
confidence: 99%